2012
DOI: 10.4111/kju.2012.53.10.716
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Dimercaptosuccinic Acid Scan May Be Related to Persistence of Vesicoureteral Reflux in Children with Febrile Urinary Tract Infection

Abstract: PurposeThis study assessed whether 99mtechnetium dimercaptosuccinic acid (DMSA) scintigraphy used for the assessment of renal sequelae after febrile urinary tract infection (UTI) has any prognostic value for outcome measurement of vesicoureteral reflux (VUR) by retrospectively evaluating the correlation between abnormal DMSA scintigraphy results and persistence of VUR in children with febrile UTI.Materials and MethodsThe medical records of 142 children (57 boys, 85 girls) admitted with febrile UTI from January… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 28 publications
3
9
0
1
Order By: Relevance
“…High sensitivity and high negative predictive value of early DMSA renal scan for VUR, as seen in this study has also been observed in some other studies [8][9][10]. Though contradicting results are observed in some studies [5,10], it has been observed that in children with dilating VUR missed out by early DMSA, development of significant renal disease was uncommon [3,12,13]. Some guidelines recommend detailed evaluation only after the second episode of febrile UTI but this may not be ideal in our population due to higher proportion of children having VUR and uncertainty in follow up.…”
Section: Discussionsupporting
confidence: 82%
“…High sensitivity and high negative predictive value of early DMSA renal scan for VUR, as seen in this study has also been observed in some other studies [8][9][10]. Though contradicting results are observed in some studies [5,10], it has been observed that in children with dilating VUR missed out by early DMSA, development of significant renal disease was uncommon [3,12,13]. Some guidelines recommend detailed evaluation only after the second episode of febrile UTI but this may not be ideal in our population due to higher proportion of children having VUR and uncertainty in follow up.…”
Section: Discussionsupporting
confidence: 82%
“…In recent study by Hyun Chong Ki "The incidence of VUR with a normal DMSA scan result was very low, and the degree of VUR in those children was low-grade and clinically insignificant." [27] and another study by Tseng et al said that "142 children with VUR and reported that all the children with grades III to V VUR (21 patients) had an abnormal DMSA scan result" [28]. These studies are agreed with the present study, most children with normal DMSA scan finding had low grade reflux.…”
Section: Us Finding During Utisupporting
confidence: 90%
“…In this study, 48 of 65 children (74%) the DMSA scintigraphy shows abnormal findings during the period of UTI while the VCUG scan study shows VUR in 75% of the children during the period of UTI. The DMSA scan study results agree with Hyun Chong Ki, in his study "abnormal DMSA scintigraphy results were found in 72.5% of children with febrile UTI" [27] but the high frequency of VCUG scan study doesn't agree with his study that have reported "VUR was found in 33.8% of the children with acute febrile UTI" [27].…”
Section: Us Finding During Utisupporting
confidence: 69%
“…Vesicourethral reflux (VUR) is defiened as retrograde passage of urine from the bladder into kidney and upper urinary tract (1,2). This condition can increase transporting bacteria from the bladder to the kidney and then predisposes patients to acute pyelonephritis (3,4).…”
Section: Introductionmentioning
confidence: 99%